PEMENUHAN HAK TERHADAP IBU DAN ANAK USIA MENYUSUI DI LEMBAGA PEMASYARAKATAN - Nazili, Aditya Choerin; Subroto, Mitro (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The fulfillment of the rights of mothers and children to breastfeed in correctional institutions is a crucial issue within the context of human rights and child welfare. This research aims to identify the challenges, policies, and practices that influence these rights, as well as their impact on the well-being of mothers and children involved in such situations. This study adopts a juridical-empirical research approach, where data is gathered through a combination of field research and literature review. Field research involves interviews with informants and respondents to collect primary data, while the literature review involves the analysis of books, literature, theories, and relevant legislation. Furthermore, this research identifies best practices and recommendations to enhance the fulfillment of the rights of mothers and children to breastfeed in correctional institutions. These recommendations encompass facility improvements, staff training, psychosocial support, and the formulation of more inclusive policies focusing on the well-being of mothers and children. The research findings also indicate that the fulfillment of these rights in correctional institutions is not yet optimal, as there are situations where mothers must bring their children to reside within these facilities. Additionally, government authorities and prison officers face various obstacles that hinder their efforts to address these issues effectively during implementation. Keywords: Prisoners' Rights; Children's Rights ; Correctional